The role of beaches in the tourism offering : the case study of the municipality of Lovran - Rudan, Elena (Array, 2018)
To position the tourism offering of the Municipality of Lovran, it must be adjusted to the modern needs of tourists. In this, a key role belongs to designing, implementing and sustaining an experience system as part of the destination’s integrated tourism product. Lovran as a tourist destination can become distinctive only to the extent to which it can provide services and facilities capable of satisfying the travel needs and motivations of tourists. When designing an experience system, the destination is generally in the focus of interest. This paper, however, takes a closer look at the thematization of beaches that are a part of Lovran’s tourism offering. Previous tourism development in Lovran has first and foremost been centred on the summer months when the sun, sea and beaches are the primary motivation for tourist arrivals. Lovran as a tourist destination, together with its beaches, provides opportunities that have yet to be fully valorised with regard to implementing the experience system in beaches. In this respect, the paper aims to highlight the need for beach thematization. Beach thematization is carried out in accordance with the vision of the destination to ensure the optimal distribution of bathers and to satisfy their preferences. A new classification of beaches is made according to the Bathing Area Registration and Evaluation (BARE) system, which is adjusted to the needs of the market. The BARE system categorises beaches based on their accessibility and coastal scenery. The purpose of the paper is to analyse beaches in Lovran and, in accordance with a beach’s potential, to propose a theme (eco beach, romantic beach, beach for families with children, etc.) for each one, based on the Regional Program for the Adaptation and Management of Seaside Beaches in Primorje-Gorski Kotar County.